Synthesis and Biological Evaluation of 2-Arylidene-4-(4-methoxy-phenyl)but-3-en-4-olides - Husain, Asif; Hasan, S.M.; Kumar, Arvind; Alam, M.M. (Asian Journal of Chemistry, 2016)
Fifteen new 2-arylidene-4-(4-methody-phynyl)but-3-en-4-olides have been synthesized by condensing 3-(4-methoxy benzoyl)propionic acid with appropriate aromatic aldehydes in presence of triethylamine. The compounds have been evaluated for their antimicrobial and antiinflammatory activities. Their structures were established on the basis of elemental analysis, IR and 1H NMR spectral data.